1998
DOI: 10.1111/j.1532-5415.1998.tb01005.x
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Wine Consumption Is Associated with Decreased Odds of Developing Age‐Related Macular Degeneration in NHANES‐1

Abstract: Moderate wine consumption is associated with decreased odds of developing AMD. Health promotion and disease prevention activities directed at cardiovascular disease may help reduce the rate of AMD-associated blindness among older people. The nature and pathophysiology of this association warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(62 citation statements)
references
References 40 publications
2
56
0
4
Order By: Relevance
“…On the other hand, many studies have revealed that alcohol consumed in smaller amounts may protect from several non-autoimmune diseases such as ischemic heart disease (1), cerebral thrombosis (2), hypertension (3), upper respiratory infections (4), gallbladder and renal stones (5,6), age-related macular degeneration (7), and dementia (8). Recently, it was shown that asthma incidence is also lower among moderate alcohol consumers compared with abstainers (9).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, many studies have revealed that alcohol consumed in smaller amounts may protect from several non-autoimmune diseases such as ischemic heart disease (1), cerebral thrombosis (2), hypertension (3), upper respiratory infections (4), gallbladder and renal stones (5,6), age-related macular degeneration (7), and dementia (8). Recently, it was shown that asthma incidence is also lower among moderate alcohol consumers compared with abstainers (9).…”
Section: Introductionmentioning
confidence: 99%
“…Moderate drinking is associated with a decreased risk of myocardial infarction, stroke, and cardiac death (1,2), as well as macular degeneration, Alzheimer's disease, and cognitive deficits (3)(4)(5)(6)(7). Although the benefits of alcohol consumption are partially related to its ability to increase high-density lipoprotein (HDL)-cholesterol and to inhibit platelets, some studies indicate that the greatest protection is due to red wine (RW), rather than beer or spirits (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…36 The authors of this report speculated that antioxidant phenolic compounds found in high concentrations in red wine may explain their finding. In Beaver Dam, wine consumption was associated with a reduction in the 15-year incidence of early AMD; however, the association did not reach statistical significance.…”
Section: Alcoholmentioning
confidence: 83%